Synonyms of Words Used in Connection with Human Behavior - Dawletmuratova, Z. U.; Sadykova, R. (European Journal of Life Safety and Stability (2660-9630), 2022)
The Karakalpak language is one of the richest national languages in terms of lexical synonyms. By making proper use of the wide range of possibilities of synonymy and its subtle semantic differences, we can make our ideas clear, concrete, and concise. Synonyms are also important in determining the relationship between the speaker and writer to the oral and written expression of thought. This is because lexical units are selected according to the author’s attitude to the incident, event, or message.